Technical efficiency of public middle schools in New York City. (February 2022) - Horrace, William C.; Rothbart, Michah W.; Yang, Yi
Abstract: Using panel data and a "true" fixed effect stochastic frontier model, we estimate persistent and transient technical inefficiency in mathematics (Math) and English Language Arts (ELA) test score gains in New York City public middle schools from 2014 to 2016. We compare several measures of transient technical inefficiency and show that around 58% of New York City middle schools are efficient in Math gains, while 16% are efficient in ELA gains. Multivariate inference techniques are used to determine subsets of efficient schools, providing actionable decision rules to help policymakers target resources and incentives.